The Relationship Between Rehabilitation Exercise Compliance And Mobility Recovery In Post-Orthopedic Surgery Patients - Sultan Akbar Ibrahim; Rezqiqah Aulia Rahmat; Rahmat Pannyiwi (International Journal of Health Sciences, 2026)
Background : Orthopedic surgery May cause mobility limitations due to muscle pain​ weakness , restricted range of motion , and tissue healing . Rehabilitation exercises are an important component of recovery , but their effectiveness is strongly influenced by patient adherence to the prescribed exercise program. Objective : To analyze the relationship between adherence to rehabilitation exercises and improvement in mobility scores among patients after orthopedic surgery. Methods : This study used a quasi-experimental one-group pretest-posttest design . The sample consisted of 60 postoperative orthopedic patients selected using consecutive sampling. Participants received a structured rehabilitation exercise program for 14 days . Exercise adherence was assessed based on the percentage of prescribed exercises completed , while mobility was assessed using mobility scores before and after the rehabilitation program. Pearson correlation and paired t- test were used for data analysis with a significance level of α=0.05. Results : The mean mobility score increased from 48.37 ± 9.14 before the rehabilitation program to 70.82 ± 8.76 after the program. The mean improvement was 22.45 points . Thirty-eight patients (63.3%) had high Adherence , 16 patients (26.7%) had moderate adherence , and 6 patients (10.0%) had low adherence . A significant positive correlation was found between rehabilitation exercise adherence and improvement in mobility scores (r=0.612; p<0.001). Conclusion : Higher adherence to rehabilitation exercises was associated with greater improvement in mobility scores among postoperative orthopedic patients . Structured rehabilitation exercises and adherence monitoring should be incorporated into postoperative orthopedic care.